Answer: [tex]\displaystyle f(x)^{-1}=x+12[/tex]
Step-by-step explanation:
First, we will rewrite the function in terms of y as in y = x - 12.
Second, we will swap the x and y values.
y = x - 12
x = y - 12
Third, we will solve for y. In other words, we will isolate the y variable and get it "by itself" on one side of the equal sign.
x = y - 12
x + 12 = y
y = x + 12
Lastly, we will change y back into terms of the function, but the inverse.
[tex]\displaystyle f(x)^{-1}=x+12[/tex]
Learn more about the inverse of a function here:
https://brainly.com/question/940569